Neuronal Cells Display Distinct Stability Controls of Alternative Polyadenylation mRNA Isoforms, Long Non-Coding RNAs, and Mitochondrial RNAs - Guvenek, Aysegul; Shin, Jihae; De Filippis, Lidia; Zheng, Dinghai; Wang, Wei; Pang, Zhiping P.; Tian, Bin (Frontiers in Genetics, 2022)
RNA stability plays an important role in gene expression. Here, using 3’ end sequencing of newly made and steady state poly(A)+ RNAs, we compare transcript stability in multiple human cell lines, including HEK293T, HepG2, and SH-SY5Y. We show that while mRNA stability is generally conserved across the cell lines, specific transcripts having high GC content and likely more stable secondary RNA structures are relatively more stable in SH-SY5Y cells as compared to the other two. These features also differentiate alternative polyadenylation (APA) 3’UTR isoforms in their stability in a cell type-specific manner. By analyzing differentiation of a neural stem cell line, we show that mRNA stability difference could contribute to gene expression changes in neurogenesis. In addition, transcripts using intronic PASs are generally less stable, especially when the intron harboring the PAS is large and has a strong 5’ splice site. Interestingly, APA isoform stability difference counters APA site choice across the cell lines, suggesting 3’ end processing activity can buffer modulation of mRNA stability. Moreover, we found that long non-coding RNAs and poly(A)+ mitochondrial RNAs are more stable in SH-SY5Y cells than the other two cell lines. Together, our results reveal multiple neuronal cell-specific stability controls, which could contribute to the gene and APA isoform expression programs that define neuronal identity.